2019
DOI: 10.3390/w11030468
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Assessment of Rainfall Characteristics in Upper Blue Nile Basin over the Period from 1953 to 2014

Abstract: Investigating the trends of hydro-meteorological variables and checking its variability are of great importance for water resources management and development in the River Nile basin. The present study aimed to analyze the rainfall variability and trends in the Upper Blue Nile Basin (UBNB) over a period from 1953 to 2014. Variability analysis showed that the basin has been suffering from variable rainfall events causing severe droughts and floods over different years. According to precipitation concentration i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 33 publications
3
12
0
Order By: Relevance
“…Furthermore, our findings are in line with other similar studies, which revealed observed trend changes in the Ethiopian highlands and elsewhere, with a mean annual temperature increase range between 0.028 • C and 1.65 • C from 1955 to 2016 [63,64]. In contrast, Samy et al [65] reported a significant decreasing trend in rainfall in the southwestern part of the Upper Blue Nile basin. SPI results indicated that all the three watersheds were affected by drought episodes in 1984/1985, 1987/1988, 1992/1993, 2000/2001, 2010/2011, and 2015/2016, which is in line with other research results of drought experiences in Ethiopia [9,66].…”
Section: Exposuresupporting
confidence: 93%
“…Furthermore, our findings are in line with other similar studies, which revealed observed trend changes in the Ethiopian highlands and elsewhere, with a mean annual temperature increase range between 0.028 • C and 1.65 • C from 1955 to 2016 [63,64]. In contrast, Samy et al [65] reported a significant decreasing trend in rainfall in the southwestern part of the Upper Blue Nile basin. SPI results indicated that all the three watersheds were affected by drought episodes in 1984/1985, 1987/1988, 1992/1993, 2000/2001, 2010/2011, and 2015/2016, which is in line with other research results of drought experiences in Ethiopia [9,66].…”
Section: Exposuresupporting
confidence: 93%
“…Upper Blue Nile River (locally known as Abay) Basin is located in the northwestern part of Ethiopia between 7 • 45 and 12 • 45 N and 34 • 05 and 39 • 45 E and has a drainage area of about 176,652 km 2 [10,13]. The topography of the UBNB (UBNB) is composed of hills, highlands, valleys, and rock peaks.…”
Section: Study Areamentioning
confidence: 99%
“…Water 2021, 13, x FOR PEER REVIEW 3 of 25 area of about 176,652 km 2 [10,13]. The topography of the UBNB (UBNB) is composed of hills, highlands, valleys, and rock peaks.…”
Section: Study Areamentioning
confidence: 99%
See 1 more Smart Citation
“…The 30 m resolution digital elevation model of the NASA Shuttle Radar Topographic Mission (SRTM) ( Figure 1) depicts that the highest elevations, exceeding ASL by 4000 m, are centered on the eastern part of the basin and steadily decline in the direction of the western exit of the basin, where the altitude is almost 483 m ASL. The majority of the UBN basin flow occurs between June and September, with the outflow from Lake Tana accounting for about 7% [36]. Teleconnections strongly influence the basin's climate, with the ENSO as a primary driver of interannual precipitation variability in the basin [37], followed by the Indian Ocean and the Gulf of Guinea [38,39].…”
Section: Study Areamentioning
confidence: 99%